Le « peuple » sous la monarchie de Louis XIII - Giuliano Ferretti (Cahiers d’Études Romanes, 2017)
This study exposes the negative vision of the people embraced by the French elites of the first 17th century. During the absolute monarchy’s construction the later was constantly considered as a resource to be exploited. Overtly critiques of this model appeared only at the end of Richelieu’s ministry.